Rancang Bangun Alat Pengujian Tekanan (Burst Test) pada Produk Plastik Tube Garnier 100ml dengan Sistem Elektropneumatik - Ahmad Bagus Asmara Dana; Heroe Poernomo; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The development of Indonesian and world manufacturing industries is currently growing very rapidly due to technological advances in various fields. As a result, consumers become more critical in choosing and determining a product or service to be used. Manufacturing company engaged in manufacturing plastic packaging in Ngoro, East Java. Complaints often occur from customers for products that often experience plastic connections that are not perfectly bonded and also the tools to carry out these tests have some disadvantages of efficient and safety levels for operators.The method used for making pressure testing equipment on 100ml garnier products with a pneumatic system to overcome these problems. The working system of this machine is to put pressure on 2 products simultaneously which will be set by selenoid valve 3/2 and the timer will automatically calculate which serves to calculate the holding time of the pressure. The process of making this machine with several stages, namely design, making drawing details, electro pneumatic system planning, fabrication and assembly stages. The results of this machine can fill optimally with a maximum pressure of 2 bars into both products in a single test with the appropriate pressure It is hoped that electrophorics will work for this testing machine